Indonesia Ministry and Non Ministry (M&NM) Institutions Cloud Computing Implementation Proposal - Sadikin, Mujiono (Proceeding Information Technology, 2013)
ABSTRACT – In the last recent years, Cloud Computing (CC) is one of well-developed information technology disciplines in termsof research and its application. Implementation of CC provides many benefits such as: efficiency, guarantee oftechnology handling and managing by them who are competent in their field, reduction of investment costs, andorganizations that use the CC become can more focus on their business or services. Costs of investment andmanagement of CC systems become cheaper if there are more organizations that utilize these resources sharingservices. Level of the resources sharing utilization is higher when organizations that use those resources have the sameinterests in the process, data, and access model to the system. There are quite a lot of legal basis, procedures, data andinformation used jointly by Ministry Institions and Non Ministry of Government Institutions (M&NMs). This paperpresents the proposed model of CC systems that can be used by those M&NMs. The proposed model is generated byperforming the analysis and synthesis approach. Analysis carried out on the common service in M&NMs and synthesisis used to construct the proposed model of M&NMs CC implementation based on the analysis results.Â Keywords: CC, Ministry, Non Ministry Institution, Main Function, Supporting Function